Management of Cracks and Defects in Mechanical Components - Sergio Baragetti (Current Approaches in Science and Technology Research Vol. 10, 2021)
This chapter reports a survey of the methods that allow assessing structural health monitoring of structural components. This issue is quite relevant in the aeronautical and aerospace sectors, but also in the industrial machines and automotive areas. Numerical models and experimental procedures will be described, even though not too much deepened. Finite Element Modelling (FEM), strain gages and replica method procedures will be reported.